Early effects of fluoro-edenite: correlation between IL-18 serum levels and pleural and parenchymal abnormalities. (December 2016) - Ledda, Caterina; Loreto, Carla; Matera, Serena; Massimino, Nicoletta; Cannizzaro, Emanuele; Musumeci, Andrea; Migliore, Marcello; Fenga, Concettina; Pomara, Cristoforo; Rapisarda, Venerando
Fluoro-edenite (FE) is a natural mineral asbestos-like fibrous species first isolated in Biancavilla, Sicily. In order to clarify potential involvement of IL-18 in the pathogenesis of FE-induced chest abnormalities, we analyzed IL-18 serum levels in FE-exposed workers (FEEW) and correlated them with pleural and parenchymal abnormalities. A total of 21 FEEWs, residing in Biancavilla for >30 years, with a working seniority of 17 ± 6.1 years were examined. High-resolution computed tomography scans revealed low grade of fibrosis in 8 (38%) FEEWs, and pleural plaques (PPs) in 13 (62%) FEEWs. The mean IL-18 level was 203.13 ± 90.43 pg/ml. Pearson correlation showed a significant association (p < 0.0001) between IL-18 and PPs and parenchymal abnormality scores. Data suggest a potential role of IL-18 in the pathogenesis of these diseases.